Promoting university community’s creative citizenry. - Jusoff, Kamaruzaman; Abu Samah, Siti Akmar; Mohd Isa, Posiah (2009)

(untitled)
Being creative in an educational environment, such as in the university, has many times been downplayed by bureaucracy, human inadequacy and physical hindran ce. These factors control, stifle and subsequently condemn this natural phenomenon which is normally exuded by the tertiary community. If taken in a positive light, creativity has always led to many new discoveries and inventions. These creations are then gradually developed for the university reputation and achievements, in all fields of studies from the sciences to the humanities. This paper attempts to explore, through more than twenty years of observation, issues that stifle the university citizenry – academicians and students’ – creativity. It also scrutinizes how enhancement of such creativity can be further supported by bureaucracy simplicity, encouraging and developing human potential and constructing uncompromising physical infrastructure and administrative support. These ideals – all of which can help to promote creativity, increases the productivity of the university community in aspects of teaching, research, publication, innovation and commercialization; be it at national as well as at international arena for the good of human and societal growth and development. This discursive presentation hopes to address another issue on promoting university community creativity through several deliverables which require cooperation from every quarter of the institution so that being creative continues to be promoted for sustainable human capital growth and development of the country, if not, the global community.